Screening For Antiyeast Activities From Selected Medicinal Plants - Siti Noor Adnalizawati Adnan; I. Darah; K. Jain; S. Suraya; S. H. Lim; N. Hazarina (Forest Research Institute Malaysia, 2024)
Indexed by SCOPUS